2021
DOI: 10.1186/s13014-020-01739-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome and pathologic correlation of stereotactic body radiation therapy as a bridge to transplantation for advanced hepatocellular carcinoma: a case series

Abstract: Background Stereotactic body radiotherapy (SBRT) is an emerging modality for hepatocellular carcinoma (HCC). However, there is scant information about its safety and effectiveness in the neoadjuvant setting prior to liver transplantation (LT). We present the clinical outcome and pathologic assessment of SBRT followed by LT for patients with advanced HCC. Methods This retrospective study included HCC patients treated with neoadjuvant SBRT prior to L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…However, from a sample size this small and above all a very short time interval between SBRT and LT in three out of four patients in the SBRT only group ( ) it cannot be ruled out that SBRT alone might be equally efficient to TACE and SBRT combination therapy. However, recently published data from a cohort of 14 patients showing complete response by histopathology in 23.1% of tumor nodules in liver explants is in line with our data[ 36 ] – indicating that complete tumor necrosis is not commonly achieved after SBRT alone.…”
Section: Discussionsupporting
confidence: 91%
“…However, from a sample size this small and above all a very short time interval between SBRT and LT in three out of four patients in the SBRT only group ( ) it cannot be ruled out that SBRT alone might be equally efficient to TACE and SBRT combination therapy. However, recently published data from a cohort of 14 patients showing complete response by histopathology in 23.1% of tumor nodules in liver explants is in line with our data[ 36 ] – indicating that complete tumor necrosis is not commonly achieved after SBRT alone.…”
Section: Discussionsupporting
confidence: 91%
“…Out-field HCC was found in eight patients, which is consistent with the above-mentioned fact that HCC is a multicentric disease. Previous studies have found similar results with good local control rates and favorable toxicity profiles [ 14 , 51 ]. In a series of 38 patients treated with SBRT, the histologic response rate (complete plus partial response) was 68% [ 52 ].…”
Section: Discussionsupporting
confidence: 59%
“…Gabr et al [ 116 ], examining 207 cases of Yttrium-90 therapy as bridging or downstaging prior to LT, reported tumor response with complete necrosis (100%) in 94% of patients, extensive necrosis (51–99%) in 29%, and partial necrosis (<50%) in 26%, with a recurrence rate of 12% after LT. SBRT is an external beam radiation therapy method that precisely delivers a high dose of radiation to an extracranial target using either a single dose or a small number of high-dose fractions. The frequency of complete pathological necrosis of the tumor after SBRT varies from 13.3% to 61.5% [ 101 , 117 , 118 ]. Wong et al [ 119 ] reported that pre-transplant SBRT had a higher frequency of complete pathological necrosis and a lower frequency of drop-outs from the waiting list compared to conventional bridging therapy.…”
Section: Variations Of Pre-transplant Locoregional Therapiesmentioning
confidence: 99%